THE APPLICATION OF KUMON METHOD WITH GRAPHICS MEDIA IN IMPROVING MATHEMATICS LEARNING ABOUT FRACTION FOR THE FOURTH GRADE STUDENTS OF SDN 2 KUTOSARI IN THE ACADEMIC YEAR OF 2015/2016 - Muflikhah, Naely (KALAM CENDEKIA PGSD KEBUMEN, 2016)
The objectives of this research are (1) describe the steps on the application of Kumon method with graphics media, (2) improve Mathematics learning about fraction. This research is conducted within three cycles are as follows: planning, action, observation, and reflection. Subjects of the research were 45 students. The conclusions of this research are as follows: (1) the appropriate steps of Kumon method with graphic media, namely (a) deliver the homework, (b) providing the graphic media, (c) complete students? worksheet, (d) scoring students? worksheet, (e) input the score, (f) correction of students? worksheet, (g) asking students? problem, (h) have practices. (2) The research show that the application of Kumon method with graphics media conducted appropriately can improve Mathematics learning about fraction for the fourth grade students of SDN 2 Kutosari in the academic year of 2015/2016. It was proven by the increase of learning outcomes in the first cycle 60%, in the second cycle 76.67%, and in the third cycle 86.67%.Keywords: Kumon method, graphic, students? learning outcomes